MOTIVASI INDONESIA BEKERJASAMA DENGAN MALAYSIA DALAM MEMBENTUK THE COUNCIL OF PALM OIL PRODUCING COUNTRIES (CPOPC) TAHUN 2015 - Gunawan, Suherno; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is intended to describe and to explain the motivation of Indonesia establishing cooperation with Malaysia in The Council Of Palm Oil Producing Countries (CPOPC). CPOPC was made to shift from competitive relation to cooperation between member countries. While Indonesia has the advantage in the market and production of Crude Palm Oil (CPO), Malaysia has been a tough competitor.In order to explain and to answer the research question,in this paper the researcher used the neoliberalism perspective. The main idea of neoliberalism is that the national interest among countries, especially when there are similarity in values, can lead to cooperation. Furthermore, the theory that the researcher used is cooperation theory.The Researcher has provided explanations why Indonesia establish a cooperation with Malaysia in The Council Of Palm Oil Producing Countries (CPOPC). Competitive relation with Malaysia has always been filled with frictions, worsen by the image of Indonesian palm oil plantation is ruining the environment. The ratification of this agreement is an option to Indonesia to achieve positive impact to Crude Palm Oil (CPO) trade.Keywords: Crude Palm Oil, Agreement, Neoliberalism, Indonesia Malaysia Cooperation, CPOPC.